Work-related rhinitis - Is it always an occupational disease? - Witold Salski; Marta Wiszniewska; Agata Salska; Diana Tymoszuk; Jolanta Walusiak-Skorupa (Nofer Institute of Occupational Medicine, 2016)
Rhinitis is a chronic inflammatory disease of the upper respiratory tract, characterized by a high prevalence and a complex pathogenesis. Work-related rhinitis (WRR) can be divided into occupational rhinitis (OR) and work-exacerbated rhinitis (WER). It is not only considered as a disease entity but also in the context of medical certification as the allergic disease associated with occupational exposure. Epidemiology of work-related rhinitis has been found to vary depending on the occupation and specific exposure, on the other hand the prevalence data may be underestimated due to the lack of uniform diagnostic criteria. This paper reviews the issues comprising the pathogenesis, epidemiology, diagnosis and treatment of patients with work-related rhinitis. It also discusses the significance of the disease in occupational medicine, particularly in terms of preventive worker care, general principles of good practice in primary and secondary WRR prevention and the necessary directions of changes in medical certification in the cases of occupational rhinitis. Med Pr 2016;67(6):801-815